Perbandingan Pengaruh Latihan Colorado Experiment dengan Burn out Terhadap Peningkatan Volume Otot Dada - Setiawan, Tedi; Hartono, Tony; Ropi, Ucu Abdul (Jurnal Keolahragaan, 2024)
The independent variables consist of the Colorado experiment and burn out. The aim of this study is to change the appearance of chest muscle volume. The research uses a pre-experimental method. Pretest-posttest two group design as the research design. The location of this study is Diamond Fitness. The total research subjects were 14 men divided into two research groups. The measuring tool used is circumference measurements only on the chest circumference. The statistical data processing process applies the SPSS 25 application. The results of this study are 1. Exercise using the Colorado Experiment system has a significant effect on increasing chest muscle volume. 2. Training using the burnout system has a significant effect on increasing chest muscle volume. 3. There is no significant difference between training using the Colorado Experiment system and burn out on increasing chest muscle volume. Conclusion: The independent variables consisting of the Colorado experiment and burnout showed better changes in chest muscle volume in Diamond Fitness members. Suggestion: A variety of exercise variations must be used so that the right training method can be found for each individual Diamond Fitness member.Variabel bebas terdiri dari colorado experiment dan burn out adalah tujuan dari studi ini untuk merubah penampilan pada volume otot dada. Penelitian menggunakan metode pre-experimen. Pretest-postest two group design sebagai desain penelitian. Lokasi studi ini adalah di Diamond Fitness. Subjek penelitian keseluruhan berjumlah 14 orang putra dibagi menjadi dua kelompok penelitian. Alat ukur yang digunakan yaitu circumference measurements hanya pada bagian lingkar dada. Proses pengolahan data statistik menerapkan aplikasi SPSS 25. Hasil studi ini adalah 1. Latihan menggunakan sistem colorado experiment memperlihatkan hasil yang lebih baik pada volume otot dada. 2. Menggunakan sistem burnout memperlihatkan hasil yang lebih baik pada massa otot dada. 3. Ke-dua metode tersebut tidak terlihat keunggulan atau sebaliknya ke-dua variabel bebas tersebut mempunyai perubahan positif yang lebih baik pada volume otot dada. Kesimpulan: Variabel bebas yang terdiri dari colorado experiment dan burnout adanya perubahan yang lebih baik untuk volume otot dada pada anggota Diamond Fitness. Saran: Berbagai variasi latihan harus digunakan agar dapat ditemukan metode latihan yang tepat bagi setiap masing-masing individu anggota Diamond Fitness.